Flow obstacle effect on film boiling heat transfer with uniform and non-uniform axial heat flux - Zahlan, Hussam (University of Ottawa (Canada), 2009)
An experimental investigation of the effects of axial flux distribution (AFD) and obstacles on film-boiling heat transfer was performed in a vertical tube using HFC-134a as coolant. The following parameters were examined: (1) Axial flux profiles (uniform, inlet-peak and outlet-peak), (2) Flow-blockage ratios (12% and 24%), (3) Obstacle pitches (150 mm and 300 mm), (4) Obstacle shapes (blunt and round). Test conditions covered the pressure 1665 and 2389 kPa (water-equivalent value: 10 and 14 MPa), a mass-flux range from 1395 to 3575 kg.m-2.s -1 (water-equivalent value: 2000 to 5000 kg.m-2.s -1) and an inlet-fluid temperature range from 30 to 70°C (water-equivalent value: 229 to 324°C). Film-boiling temperature measurements were recorded for all possible heat-flux levels, up to a limiting surface temperature of 240°C to avoid Freon decomposition. Inside wall temperature distributions of the obstacle-equipped test sections were compared against those of a reference bare tube at similar flow conditions. Flow obstacles were found to have a significant influence on film-boiling heat-transfer. Film-boiling wall temperatures along the test section were reduced significantly by decreasing the obstacle pitch, by increasing the obstacle size and by using a blunt instead of streamline-shaped obstacle. The effect of AFD on film-boiling heat transfer is noticeable in the developing film-boiling region and can be attributed mainly to the variation in critical heat flux (CHF) occurrence. However, the AFD effect appears to be less obvious in the fully developed film-boiling region. Since the literature suggested that the single-phase pressure-loss coefficient of the flow obstructions could be an important parameter in correlating the film-boiling heat-transfer enhancement, this parameter was also measured and correlated. Previously derived prediction methods for obstacle-enhanced film-boiling heat transfer did not provide satisfactorily agreement with the data; therefore, a new prediction method was derived to predict the film-boiling heat-transfer augmentation for uniform AFD tubes. The new equation accounts for the enhancement in film-boiling heat transfer due to turbulence generated by (i) liquid-film termination at the dryout point and (ii) the upstream flow obstructions. The new correlation was applied to non-uniform AFD data. It was concluded that (i) this new prediction method is also applicable to non-uniform AFD tubes, (ii) the new prediction method has the correct asymptotic trends and (iii) single-phase pressure-loss coefficients cannot be used directly to predict the heat-transfer enhancement for both blunt and rounded obstacles.
Keywords: Engineering, Mechanical.